2019
DOI: 10.3390/jcm8050745
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurements of Breast Density Using Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis

Abstract: Breast density, a measure of dense fibroglandular tissue relative to non-dense fatty tissue, is confirmed as an independent risk factor of breast cancer. Although there has been an increasing interest in the quantitative assessment of breast density, no research has investigated the optimal technical approach of breast MRI in this aspect. Therefore, we performed a systematic review and meta-analysis to analyze the current studies on quantitative assessment of breast density using MRI and to determine the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Previous studies have reported that the potential risk of breast cancer in women with dense breasts is three- to five-fold higher than in women with fatty breasts [ 5 , 6 , 7 ]. Recent developments in breast cancer screening have intensified the need for a standardized imaging protocol and/or measurement method for the evaluation of breast density predominantly for women at an elevated risk of developing breast cancer, such as those with high breast density [ 4 , 8 , 9 , 10 ]. A considerable amount of literature has been published on the assessment of breast density with several methods and algorithms proposed to segment and/or measure breast density using MRI datasets [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that the potential risk of breast cancer in women with dense breasts is three- to five-fold higher than in women with fatty breasts [ 5 , 6 , 7 ]. Recent developments in breast cancer screening have intensified the need for a standardized imaging protocol and/or measurement method for the evaluation of breast density predominantly for women at an elevated risk of developing breast cancer, such as those with high breast density [ 4 , 8 , 9 , 10 ]. A considerable amount of literature has been published on the assessment of breast density with several methods and algorithms proposed to segment and/or measure breast density using MRI datasets [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research has consistently shown that these methods/algorithms seem to have certain drawbacks, mostly due to the use of a semi-automatic approach or a high-level of dependency on user interaction. Likewise, numerous MR breast-imaging protocols have been applied to the screening and/or the assessment of breast density, ranging from contrast- to non-contrast-enhanced imaging with or without the implementation of fat-suppression techniques [ 3 , 4 , 8 , 9 , 10 , 20 , 21 , 22 , 23 , 24 , 25 ]. To date, there has been little consensus on the optimal MR breast-imaging protocol and measurement method for breast density screening and/or assessment, especially in the context of women with dense breast tissues.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations